2018
DOI: 10.1088/1361-6463/aaddea
|View full text |Cite
|
Sign up to set email alerts
|

Sb2(S1−x Se x )3 solar cells: the impact of radiative and non-radiative loss mechanisms

Abstract: The compound Sb2(S1−xSex)3 has recently attracted a great deal of attention from the scientific community for solar cell applications. However, Sb2(S1−xSex)3 inorganic solar cell efficiencies are still limited to values lower than 7%, further studies contributing to a better understanding of the limiting factors behind this technology being necessary. In particular, no theoretical works on Sb2(S1−xSex)3 solar cell modeling have been previously reported. In this work, we present results on Sb2(S1−xSex)3 solar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 52 publications
3
30
0
Order By: Relevance
“…To the best of our knowledge, no study has addressed this issue prior to our work. [28] We have reported for the first time a theoretical study to seek for an explanation of the origin of these low efficiencies. We have modelled Sb2(Se1-xSx)3 under the radiative and non-radiative limit varying the compositional ratio Se/(S+Se) in a range of 0 ≤ x ≤ 1 and the thickness of the absorber.…”
Section: Theoretical Analyses Of Sb 2 (S 1-x Se X ) 3 Semiconductor Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, no study has addressed this issue prior to our work. [28] We have reported for the first time a theoretical study to seek for an explanation of the origin of these low efficiencies. We have modelled Sb2(Se1-xSx)3 under the radiative and non-radiative limit varying the compositional ratio Se/(S+Se) in a range of 0 ≤ x ≤ 1 and the thickness of the absorber.…”
Section: Theoretical Analyses Of Sb 2 (S 1-x Se X ) 3 Semiconductor Materialsmentioning
confidence: 99%
“…Efficiency of Sb2(S1-xSex)3 solar cell considering Se/ (S+Se) compositional ratio as a function of (a) absorber thickness under the radiative limit, (b) minority carrier lifetime. [28] On the other hand, we made the analysis of the possible impact of recombination centers under the non-radiative limit employing the Shockley-Read-Hall theory. [59] We found that the conversion efficiency decays from 28% (absorber with a minority carrier lifetime of 1 ns) to 2% for very low minority carrier lifetimes of around 10 -10 s (Figure 5b).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4 illustrates results on efficiency (η), short-circuit current density (J sc ), open-circuit voltage (V oc ), and fill factor (FF) of CZTSSe solar cells as functions of the S/(S+Se) compositional ratio considering an absorber thickness of 2 μm. Details of the calculation procedure and parameters can be found in the literature [24,25]. Under the radiative limit, efficiency values in the range of 26.3%-29.6% are expected, markedly higher than the experimental values reported for this technology.…”
mentioning
confidence: 97%
“…Further details on calculations can be found in reference. [14] The impact of SnSe thickness on open-circuit voltage, short-circuit current density, and efficiency is illustrated in Figure 1. It is observed that maximum open-circuit voltage values in the range of 624-702 mV are expected under the radiative limit.…”
mentioning
confidence: 99%